Investigation of laser sintering of pharmaceutical excipients for oral solid dosage forms - Mitrousi, Marina-Eirini (2022)
Additive Manufacturing (AM) of medication has offered great potential to the pharmaceutical industry in recent years, specifically for its revolutionary potential for personalised medicine. The replacement of conventional drug manufacture and distribution could provide patients with customised drug dosages fabricated at the point of care to reduce cost and enhance therapy adherence. Laser Sintering is a powder-based AM technique with potential for use in pharmaceutical applications. It is a solvent-free process that does not require support structures compared to other AM processes, providing increased stability and productivity in comparison to other AM techniques such as extrusion. Laser Sintering relies on consolidation mechanisms achieving high mechanical properties, and further it offers unlimited design freedom and industrial scale opportunities. However, there are limitations that prevent rapid deployment of Laser Sintering in pharmaceutics mainly due to the narrow variety of applicable polymer based excipient materials, which results from the complex thermal processing conditions. Most materials do not make it through the development stages in Laser Sintering, which makes it necessary to understand the most important factors that influence processing and part properties to enable design and development of drug dosage forms by this technology. This PhD studied the potential of using Laser Sintering for the fabrication of oral solid dosage forms (tablets) using placebo formulations. To achieve this, characterisation and processing of several pharmaceutical grade polymers was performed to identify candidate materials. Primarily, Laser Sintering showed potential for processing pharmaceuticals, however all the investigated materials presented important incompatibilities that impacted their processability. Materials with high moisture content experienced dehydration, which led to degradation upon the application of the laser beam. Furthermore, increased moisture levels induced cohesiveness and prevented the deposition of uniform layers of powder. Processing materials consisting of large and irregular particles introduced porosity and shrinkage, while processing of fine particle grades generated high electrostatic forces causing agglomeration and limiting powder flow. However, among the tested materials, Eudragit L100-55, a methacrylic acid ethyl acrylate copolymer known for its use as a coating agent in drug dosage forms, although an amorphous polymer it exhibited acceptable sinter-ability due to its ideal particle morphology and distribution that resulted in high packing efficiency and part density. Eudragit L100-55 and Avicel 101, a microcrystalline cellulose grade pharmaceutical popularly used as a diluent, were used for the development of preliminary formulations for the preliminary assessment on Laser Sintering of oral solid dosage forms. Avicel 101 demonstrated poor sinter-ability due to its unfavourable thermal characteristics, which resisted particle fusion and experienced degradation. Processing of the two materials together was proved viable by direct sintering of Eudragit L100-55 as a matrix to bind together the solid particles of Avicel 101. However, the presence of unmolten Avicel 101 particles increased the number of voids and promoted structural porosity. The increased porosity enhanced fragility of the parts, which impacted the mechanical properties resulting in poor strength, friability and stiffness. The poor mechanical performance significantly reduced the tablet integrity, which was translated in poor pharmaceutical functionality, demonstrating rapid disintegration. To enhance the processability of the powders and enable the production of oral solid dosage forms with increased functionality, an alternative approach was taken to produce an optimal pharmaceutical material for Laser Sintering. Exploiting the pH-dependent solubility of Eudragit L100-55, polymer precipitation and evaporation methods were used in a simple cost-effective system to create a film coating on Avicel 101 particles. The methods proved suitable to produce a film on the surface of Avicel 101 particles and they were simple and easy to reproduce. The development of a coated cellulose-base material aimed at the production of parts with increased density and mechanical strength, compared to the powder blends. This coating approach could have wide implications for Laser Sintering providing a new route for materials development for Laser Sintering that can open the way for innovative opportunities in pharmaceutics and broader, enabling the selection of a greater list of materials for further adoption of Laser Sintering in a wider range of applications.